2021
DOI: 10.1016/j.ejca.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survival in women diagnosed with pregnancy-associated cancer: An overview using nationwide registry data in Sweden 1970–2018

Abstract: Background: Pregnancy-associated cancer (PAC) is increasing over time in many countries. We provide a comprehensive, population-based overview of cancer survival in women with PAC across five decades. Methods: We performed a nationwide cohort study of 121,382 women diagnosed with cancer at age 15e49 between 1970 and 2018 using birth and cancer registers in Sweden. Pregnancy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…There may also be biases, as the NCDB and NCCN Breast Cancer Outcomes DB are not population-based databases and only consider the care of those who had access to and received treatment at major academic cancer centers. Such biases can be ruled out in the exhaustive population-based registries of northern European countries such as Sweden, Norway, Finland, and Denmark [ 16 , 17 , 18 , 19 ]. We report here a much larger cohort of BC patients, which could be used for studies with high statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be biases, as the NCDB and NCCN Breast Cancer Outcomes DB are not population-based databases and only consider the care of those who had access to and received treatment at major academic cancer centers. Such biases can be ruled out in the exhaustive population-based registries of northern European countries such as Sweden, Norway, Finland, and Denmark [ 16 , 17 , 18 , 19 ]. We report here a much larger cohort of BC patients, which could be used for studies with high statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be biases, as NCDB and NCCN Breast Cancer Outcomes DB are not population-based databases and only consider the care of those who had access to and received treatment at major academic cancer centers. Such biases can be ruled out in the exhaustive population-based registries of northern European countries such as Sweden, Norway, Finland and Denmark (de Boniface et al, 2021; Christiansen et al, 2016; Johansson et al, 2021; Leinonen et al, 2017). We report here a much larger cohort of BC patients, which could be used for studies with high statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…European countries such as Sweden, Norway, Finland and Denmark (de Boniface et al, 2021;Christiansen et al, 2016;Johansson et al, 2021;Leinonen et al, 2017). We report here a much larger cohort of BC patients, which could be used for studies with high statistical power.…”
Section: Such Biases Can Be Ruled Out In the Exhaustive Population-ba...mentioning
confidence: 99%
“…At present, there were still great differences in the prognosis of PABC. Data from Sweden showed that PABC was associated with a poor prognosis compared with non-PABC, comparing the 5-year and 10-year survival rates, it was found that the agestandardized survival rate of women with breast cancer during pregnancy was similar to that of non-PABC over time, while postpartum breast cancer was still lower [22]. Some studies had found similar results, suggesting that breast cancer diagnosed during pregnancy was a different entity from postpartum breast cancer, and the poor prognosis of PABC was mainly attributed to the poor prognosis of postpartum breast cancer [2,6,35].…”
Section: Introductionmentioning
confidence: 98%